(untitled) (Książnica Śląska, 2025)
The article discusses the subject of German-Polish relations in the field of cultural cooperation in Upper Silesia in the years 1919–1939. The initial point for reflection is literary texts, essays and articles published in German-language magazines “Der Oberschlesier” and “Die Brücke – Most”. There were analyzed and critically assessed various statements by German historians, regionalists, writers, publishers and journalists, such as Karl Kaisig, Heinrich Koitz or August Scholtis, about poetry and prose written in Polish in Upper Silesia and about German-Polish cultural exchange. The analysis proves that magazines, on the one hand, served as bridge builders in the process of agreement between two nations, on the other, they were a tool of political propaganda focused on shaping the attitudes and opinions of their readers. It should be emphasized that only a small group of German journalists and historians knew and read Polish literature. The summary reflection recalls the important monograph of the German literary scholar and writer Arno Lubos, “Geschichte der Literatur Schlesiens”.